Akuntabilitas Kekuasaan Kehakiman - Rahayu Prasetianingsih (Jurnal Konstitusi, 2011)
Accountability in Indonesia has been known the extent of the public administration within the executive power, while for representative bodies and judicial power is only in the system administration. Public demands for accountability from all over the government institution are no exception of judicial power. It’s triggered by “mafia peradilan” issue and other distrust so it needs judicial accountability. Problems arise when faced with the principles of accountability and independence and impartiality   of the judiciary. But in fact these two principles is not the core problem of accountability judiciary, there’s  many factors  influence.